R programming fundamentals : deal with data using various modeling techniques - Medeiros, Kaelen (Packt Publishing Ltd, 2018)
Data analysis is crucial to accurately predict the performance of an application. The book begins by getting you started with R, including basic programming and data import, data visualization, pivoting, merging, aggregating, and joins. Once you are comfortable with the basics, you can read ahead and learn all about data visualization and ...